1965
DOI: 10.1136/bmj.2.5472.1215
|View full text |Cite
|
Sign up to set email alerts
|

Plasma renin concentration in human hypertension . II. Renin in relation to aetiology.

Abstract: In previous papers (Brown et al., 1965a(Brown et al., , 1965b we have demonstrated, in clinical hypertension, a close inverse relationship between renin concentration and plasma sodium which appears to be independent of aetiology, the height of the arterial pressure, complications, and treatment. The present communication is concerned with an analysis of renin and sodium in hypertension in relation to aetiology. The methods used in this study are as given previously (Brown et al., 1965b(Brown et al., , 1965d; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0
1

Year Published

1968
1968
1991
1991

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(26 citation statements)
references
References 30 publications
2
23
0
1
Order By: Relevance
“…There was a significant reciprocal correla tion between these values. This finding may be comparable to the reports that PRA values are inversely correlated to the sodium concentration in plasma (Brown et al 1965), since plasma osmolality is largely dependent upon the concentration of plasma sodium. These results may also support the concept that RA-system is closely related to the physiological control of the homeostasis in body fluid and electrolyte.…”
Section: Hyperthyroidismsupporting
confidence: 76%
“…There was a significant reciprocal correla tion between these values. This finding may be comparable to the reports that PRA values are inversely correlated to the sodium concentration in plasma (Brown et al 1965), since plasma osmolality is largely dependent upon the concentration of plasma sodium. These results may also support the concept that RA-system is closely related to the physiological control of the homeostasis in body fluid and electrolyte.…”
Section: Hyperthyroidismsupporting
confidence: 76%
“…101 Although PRA may be normal in humans with long-standing, predominantly unilateral renovascular hypertension, its level is never low nor does it closely correlate with the degree of blood pressure elevation. 102 Yet hypertension will respond to converting enzyme inhibition in this stage. 103 The possibility must be considered that local renin-angiotensin action, rather than the circulating concentrations of these substances, is what determines the level of blood pressure and organ damage.…”
Section: Phase III or The Systemic Renin-angiotensin Independent Phasementioning
confidence: 99%
“…For this reason, investigators have recently become interested in the renin levels of peripheral blood, or in blood samples taken directly from renal veins for preoperative diagnosis of renovascular hypertension.1 2,5,6,7,13,14 Experience has indicated that this method also may frequently lead to misdiagnosis because of false positive and false negative results.2 5,13,15 Consequently, we began, 4 years ago, to measure renal venous renin levels after hydralazine infusion to improve the diagnostic …”
mentioning
confidence: 99%